90 Effectiveness of an Educational Program on Beef Bull Selection that Incorporates Classroom Instruction and a Mock Auction. (30th November 2020) - Bullock, Darrh; VanValin, Katherine; Lehmkuhler, Jeffery; Anderson, Leslie; Crites, Benjamin; Laurent, Kevin; Spangler, Matthew L; Weaber, Robert
Abstract: An educational program was developed to assist beef producers with making informed bull purchasing decisions. There are two core pieces to this decision: targeting the bull's genetics to the producer's management and resources, and paying a price that maximizes the return on investment. This was a two-part educational program; the first session was classroom instruction with topics related to proper bull selection. At the conclusion of this session producers were assigned one of five management scenarios and received a sale catalogue with 60 bulls. Videos of all bulls were made available, along with all production information, including adjusted measurements, EPD and indices. The producers were tasked with returning the next week to attend the mock auction and purchase the best valued bull for their assigned scenario. At the conclusion of the auction, each scenario was discussed and the individual that purchased the best value bull in each scenario was recognized. Value was determined as the price paid for the bull compared to a price determined through an "economic selection index" equation. Beef producers (n = 322) participated in the program over 9 locations; in locations with less attendance, a reduced sale catalogue was used. Of the post-program survey respondents (n = 155), 71% were commercial beef producers, 27% were seedstock producers and 5% were Extension agents (n = 10, were cross classified). When asked how much time they spent reviewing the materials before the mock sale 8% said they made their decision at the sale, 16% spent 30 minutes or less, 58% spent 30 minutes to 2 hours and 18% spent over 2 hours preparing. When asked if the program would help with their next bull purchase, 88% said it would probably or definitely help. The conclusion was that this was a valuable educational program.